Synthesis of an aromatic N-heterocycle derived from biomass and its use as a polymer feedstock - Yu Qi (Nature Portfolio, 2019)
Aromatic N-heterocyclic compounds are important chemicals, but produced from petroleum. Here the authors show a pyridazine-based compound 6-(4-hydroxy-3-methoxyphenyl)pyridazin-3(2H)-one, used as polymer feedstocks, can be synthesized by a Friedel-Crafts reaction from biomass starting materials.